Prenatal diagnosis of genetic diseases - Serra, Angelo (Medicina e Morale, 2024)
For the last fifteen years or so, the application of new techniques has entered medical practice, and has become widespread, that make it possible to establish the existence of particular conditions in the foetus, capable of causing alterations in its development or giving rise to serious pathologies later or later after birth. Techniques therefore offering the possibility of making prenatal genetic 'diagnoses' and 'prognoses'.